Effect Of Mulching and Sulphur Doses on Growth and Yield of Groundnut in Rampur, Chitwan, Nepal: - Bhattarai, Prerana; Pokhrel, Manisha; Lohani, Surakshya; Sapkota, Sandhya; Shrestha, Susmita; Khadka, Bishal; Kalauni, Sunil Datta (International Journal of Applied Sciences and Biotechnology, 2025)
Groundnut (Arachis hypogea. L) commonly known as peanut, is valued for its multiple uses including both human and animal consumption in the form of food, oil, and fodder, as well as acting as an effective fertilizer. Its productivity is affected by different management practices as well as nutrients. This study examines the effects of mulching (no mulch vs. rice husk mulch) and various doses of Sulphur (0, 25, 35, and 45 kg/ha) on growth, yield attributes, and yield of groundnut under field conditions. The research conducted showed that rice husk mulching positively correlated with vegetative growth, including plant height, number of branches, canopy area, number of flowers, pod weight, and biological yield compared to no mulching. Similarly, among different Sulphur levels, 35-45kg/ha showed outstanding performance on pod yield, kernel number, shelling percentage, and harvest index. So, integration of mulching with an appropriate Sulphur dose can help both increase the vegetative as well as reproductive growth of groundnut. Int. J. Appl. Sci. Biotechnol. Vol 13(4): 171-179.